2010
DOI: 10.3233/jad-2010-1378
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine, Mental Health, and Psychiatric Disorders

Abstract: Abstract. Caffeine intake is so common that its pharmacological effects on the mind are undervalued. Since it is so readily available, individuals can adjust their own dose, time of administration and dose intervals of caffeine, according to the perceived benefits and side effects of each dose. This review focuses on human studies of caffeine in subjects with and without psychiatric disorders. Besides the possibility of mild drug dependence, caffeine may bring benefits that contribute to its widespread use. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 125 publications
(141 reference statements)
3
135
0
6
Order By: Relevance
“…Interestingly, despite being anxiogenic in Wistar rats in the elevated plus maze, caffeine actually increased open arm time after the rats underwent a chronic, unpredictable stress procedure (Pechlivanova et al, 2010), a method to model depression in rodents. This reduction in anxiety-like behavior by caffeine in the context of depression may be related to other evidence suggesting that moderate caffeine intake (< 6 cups/day) was associated with less depression and a lower risk of suicide (Lara, 2010). This suggests that different mechanisms may underlie the pathogenesis of anxiety and depression, despite their cooccurrence in many psychiatric diseases, and that both may involve changes in adenosine signaling.…”
Section: Caffeinementioning
confidence: 82%
See 2 more Smart Citations
“…Interestingly, despite being anxiogenic in Wistar rats in the elevated plus maze, caffeine actually increased open arm time after the rats underwent a chronic, unpredictable stress procedure (Pechlivanova et al, 2010), a method to model depression in rodents. This reduction in anxiety-like behavior by caffeine in the context of depression may be related to other evidence suggesting that moderate caffeine intake (< 6 cups/day) was associated with less depression and a lower risk of suicide (Lara, 2010). This suggests that different mechanisms may underlie the pathogenesis of anxiety and depression, despite their cooccurrence in many psychiatric diseases, and that both may involve changes in adenosine signaling.…”
Section: Caffeinementioning
confidence: 82%
“…Research has revealed that adenosine signaling is central to the anxiety regulating effects of these drugs. While people can benefit from many of the effects of adenosine receptor antagonism by caffeine, such as increased alertness, improved attention or focus, and even amelioration of depressive symptoms (Lara, 2010), sensitivity to caffeine-induced anxiogenesis may preclude certain individuals from enjoying coffee, tea, cola, or chocolate. On the other hand, moderate doses of alcohol are anxiolytic, and sensitivity to this effect may lead a person to abuse alcohol.…”
Section: Regulation Of Adenosine Signaling By Caffeine and Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most prevalent complications of AD is depression of mood, and the recent observations that caffeine might be a mood normalizer are of particular interest [29]. Given that the consumption of caffeine is associated with a reduced risk of depression [30], this may be a further potential confounding factor to be taken into account when designing a study to probe the ability of caffeine to preserve memory function in AD patients.…”
Section: S251mentioning
confidence: 99%
“…Given that the consumption of caffeine is associated with a reduced risk of depression [30], this may be a further potential confounding factor to be taken into account when designing a study to probe the ability of caffeine to preserve memory function in AD patients. Likewise, several other beneficial effects of caffeine on arousal and motivation [31,32] as well as other psychiatric conditions [29] should also be considered.…”
Section: S251mentioning
confidence: 99%